Australia's Economy in its International Context: The Joseph Fisher Lectures (vol. 2) - Anderson, Kym (University of Adelaide Press, 2021)
This two-volume collection brings together the first 53 Joseph Fisher Lectures in economics and commerce, presented at the Adelaide University every other year since 1904. Funds for the Lectures, together with a medal for the top accounting student each year, were kindly provided by a £1,000 endowment to the University by the prominent Adelaide businessman Joseph Fisher in 1903. The Lectures address a wide range of Australian economic issues, in addition to some international economic issues of national significance. They have stood the test of time extremely well, while also providing a reminder of the events and concerns that were prominent at different times during the past century.